(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the significance of economic resilience as a key factor in the long-term economic stability of Uzbekistan. It provides a theoretical overview of both classical and modern approaches to economic resilience, including the Solow model and endogenous growth theory. Special attention is given to the analysis of macroeconomic indicators of the Republic of Uzbekistan over the period from 2013 to 2023, with a focus on real GDP growth rates. The study identifies major challenges such as inflation, income inequality, investment dependency, and environmental issues. It proposes strategies to enhance the sustainability of growth through institutional reforms, support for innovation, and a transition to a green economy. The article concludes that combining quantitative indicators of growth with qualitative improvements in education, healthcare, and environmental protection is essential for achieving long-term socio-economic resilience.